Position Specific Alternative Splicing and Gene Expression Profiles Along the Tonotopic Axis of Chick Cochlea - Koo, Heiyeun; Hwang, Jae Yeon; Jung, Sungbo; Park, Hyeyoung; Bok, Jinwoong; Park, Juw Won (Frontiers in Molecular Biosciences, 2021)
Alternative splicing (AS) refers to the production of multiple mRNA isoforms from a single gene due to alternative selection of exons or splice sites during pre-mRNA splicing. It is a primary mechanism of gene regulation in higher eukaryotes and significantly expands the functional complexity of eukaryotic organisms, contributing to animal development and disease. Recent studies have shown that AS also influences functional diversity by affecting the transcriptomic and proteomic profiles in a position-dependent manner in a single organ. The peripheral hearing organ, the cochlea, is organized to detect sounds at different frequencies depending on its location along the longitudinal axis. This unique functional configuration, the tonotopy, is known to be facilitated by differential gene expression along the cochlear duct. We profiled transcriptome-wide gene expression and AS changes that occur within the different positions of chick cochlea. These analyses revealed distinct gene expression profiles and AS, including a splicing program that is unique to tonotopy. Changes in the expression of splicing factors PTBP3, ESRP1, and ESRP2 were demonstrated to contribute to position-specific AS. RNA-binding motif enrichment analysis near alternatively spliced exons provided further insight into the combinatorial regulation of AS at different positions by different RNA-binding proteins. These data, along with gene ontology (GO) analysis, represent a comprehensive analysis of the dynamic regulation of AS at different positions in chick cochlea.